Design of a Novel Chitosan Derivatives and DOPO Flame Retardant and Its Application in Epoxy Resin - Yicheng Yang; Yue Lu; Wang Zhan; Qinghong Kong (Macromol)
To expand the utilization of bio-based materials as flame retardants in epoxy resin (EP), a green Schiff base structural material (CSV) was synthesized via a one-pot approach employing chitosan and vanillin as the raw materials. Then, the CSV combined with 9,10-dihydro-9-oxa-10-phospha-phenanthrene-10-oxide (DOPO) (the mass ratio between CSV and DOPO was 1:2, written as CSV-DOPO) improved the flame retardancy of the EP. When the amount of CSV−DOPO in the EP was only 3 wt%, the thermogravimetric analysis (TGA) results indicated that the residue of the EP composites was 50.6% higher than that of the EP. The combustion class of the EP/3 wt% CSV−DOPO composites achieved a UL-94 V0 rating and the limit oxygen index (LOI) reached 34.0%. The cone calorimeter test (CCT) showed that the peak heat release rate (PHHR), total heat release (THR), total smoke release (TSP), and peak carbon dioxide production (PCO2P) of the EP/3 wt% CSV−DOPO composites decreased by 32.3%, 22.0%, 4.6%, and 51.0%, respectively, compared to the EP. The flame-retardancy mechanism was studied by scanning electron microscopy (SEM) and Raman spectra. The quenching effect of phosphorus-containing radicals, the dilution effect of noncombustible gases, and the impeding effect of the carbon layer in the condensed phase contributed collectively to the excellent flame retardancy of the EP/CSV−DOPO composites. Considering the facile preparation method and small addition amount of the flame retardant, the present work provides a convenient solution for the preparation of modified EP with good flame retardancy and heat stability, which is expected to be widely used in industries.